A Multicurve Cross-Currency LIBOR Market Model - Wamwea, Charity; Ngare, Philip; Bidima, Martin Le Doux Mbele (Hindawi, 2019)
Afer the dawn of the August 2007 fnancial crisis, banks became more aware of fnancial risk leading to the appearance of nonnegligible spreads between LIBOR and OIS rates and also between LIBOR of diferent tenors.Tis consequently led to the birth of multicurve models. Tis study establishes a new model; the multicurve cross-currency LIBOR market model (MCCCLMM). Te model extends the initial LIBOR Market Model (LMM) from the single-curve cross-currency economy into the multicurve cross-currency economy. Te model incorporates both the risk-free OIS rates and the risky forward LIBOR rates of two diferent currencies. Te established model is suitable for pricing diferent quanto interest rate derivatives. A brief illustration is given on the application of the MCCCLMM on pricing quanto caplets and quanto foorlets using a Black-like formula derived from the MCCCLMM.